Regarding the improvement of organizational and legal regulation of relations in the sphere of protection and use of the animal world and combating poaching during the period of martial law in Ukraine - I. D. Kazanchuk (Bulletin of Kharkiv National University of Internal Affairs)
The current state of administrative and legal regulation of social relations in the sphere of protection and use of the animal world in Ukraine is analyzed. The meaning of the concept of “poaching” is revealed and its components are outlined. Taking into account statistical data, a detailed description of effective organizational and legal measures to counter poaching cases, which are used in the activities of the units of the National Police of Ukraine, the State Ecological Inspection, and other nature protection bodies of Ukraine, is provided. It is noted that poaching is one of the major threats to biodiversity and national ecological security of Ukraine. It is emphasized the need to involve the public in the organization of actions for the protection of the animal world, as well as in the process of planning joint preventive measures of protection nature, conducting information and explanatory work among the population on issues of preventing violations of administrative (nature protection) legislation.